2022
DOI: 10.1039/d2cc04056e
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical alkynylation of hydrosilanes by iron catalysis

Abstract: Alkynylsilanes is one kind of essential synthetic block in organic chemistry. The established synthetic routes remain some drawbacks regarding to harsh reaction conditions or expensive/rare metal catalyst. Herein, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Based on the above facts and relevant literature reports, 14 we propose a plausible reaction mechanism (Fig. 4).…”
Section: Resultssupporting
confidence: 54%
“…Based on the above facts and relevant literature reports, 14 we propose a plausible reaction mechanism (Fig. 4).…”
Section: Resultssupporting
confidence: 54%
“…The photochemistry plays indispensable roles in organic synthesis since it could facilitate the formation of the reactive single-electron species and enable inert bond cleavages under mild conditions . Among them, the photoinduced iron catalysis has significantly drawn chemists’ attention since iron is the most abundant and low-cost transition metal. , The early works have disclosed that, in the presence of visible light, the excited iron catalyst might typically undergo the ligand-to-iron charge transfer (Fe­(III)–X to Fe­(II) and X·) and then facilitate the formation of the reactive carbon radicals, particularly the unstabilized alkyl radicals, by cleaving the C–H or O–H bonds (Scheme -i), providing efficient tools to construct C–C, C–N, C–O, and C–X bonds . Studies have typically focused on (i) radical addition to the unsaturated units (Scheme -i, path a), such as electron-deficient alkenes, diazene diesters, (hetero)­aryl rings, RNO x , O 2 , etc., to form bonds by the radical delivery and (ii) the radical trapping with electrophilic halogen reagents, such as NIS, NBS, or Selectfluor, to build the C–X bonds (Scheme -i, path b) .…”
mentioning
confidence: 99%
“…In this process, they found that the optimal conditions involved a combination of light, 10 mol% of iron(III) chloride, and 0.5 equivalents of lithium chloride in acetonitrile at room temperature (Figure 30). [141] The procedure worked selectively in the presence of various ethynyl phenyl sulfones and hydrosilanes ( e. g ., Ph 2 SiH 2 , Et 3 SiH, PhMe 2 SiH, etc .). The formation of silyl radicals was validated through various experiments.…”
Section: Synthesis Of 1‐silyl‐1‐alkynesmentioning
confidence: 99%